Political uncertainty and the stock market: The U.S. presidential elections - Juntunen, Veera Leena Marjatta (My University, 2021)
Recently political uncertainty has shown how vital a role it plays in the financial markets and why it is essential to understand its function. In 2020 political uncertainty rose to a record high level due to the Covid-19 pandemic, which was also dramatically reflected in the financial markets. It broadly refers to uncertainty about the future actions of the government. This means that presidential elections are an example of a source of it. This research examines the impact of political uncertainty on the stock market during the presidential elections in the United States. Previous literature has found that political uncertainty has a negative effect on stock prices because it needs a risk premium. This means that political uncertainty leads to an increased discount rate which in turn leads to a decrease in stock prices. This implies that it is priced. This research focuses on the Dow Jones Industrial Average index, but the analysis is extended to cover panel data on fifty companies selected from the Dow Jones Industrial Average and Nasdaq 100. Using monthly data from February 2000 to December 2020, this thesis examines the relationship between monthly returns and political uncertainty. The data used in this research is retrieved from Refinitiv Workspace, the website of Economic Policy Uncertainty and the Federal Reserve Bank of St. Louis. The study uses linear regression to examine the influence of political uncertainty on the stock market index, and for the investigated companies, panel regression is used. The results show that there is a negative relationship between political uncertainty and the stock market. In addition, this research reveals that during 2000—2020 political uncertainty caused by presidential elections has a negative impact on the stock market and stock returns. However, each presidential election has a different effect on stock returns. The harmfulness of previous policies can explain the differences in the influence of political uncertainty created by different presidential elections. Generally, the impact of political uncertainty is negative, but when the previous policies are detrimental enough, the impact can be positive, but often the impact is then insignificant because the change was already expected by market participants. Moreover, political uncertainty caused by the presidential elections that led to the victory of a Democrat has a more negative impact on the stock returns than political uncertainty caused by the election of a Republican candidate because the Republican party is seen as a party that is more in favour of business. Furthermore, different companies are impacted by political uncertainty differently. Larger companies are less negatively impacted by it because they are more stable than small companies. Additionally, companies doing well in corporate social responsibility are less negatively affected by it.
Keywords: political instability; presidential elections; financial markets; enterprises; regression analysis; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance